19/08/2019 05:55 PM
If y is a function of x, then the equation would be written as a "y =" equation, not an "x = " equation. This example is one where x is a function of y.
x = - 5, x = - 1
To find the x- intercepts let f(x) = 0, that is
x² + 6x + 5 = 0 ← in standard form
Consider the factors of the constant term (+ 5) which sum to give the coefficient of the x- term ( + 6)
The factors are + 5 and + 1, since
5 × 1 = 5 and 5 + 1 = + 6, hence
(x + 5)(x + 1) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 5 = 0 ⇒ x = - 5 ⇒ (- 5, 0 )
x + 1 = 0 ⇒ x = - 1 ⇒ (- 1, 0)
(0, 1), (1, 3), (2, 9), (3, 27)
The first and third options are completely out because the y-value of an exponential function is never zero.
For the second option the y-values has no geometric pattern or common ratio.
For the last option, we can observe the following pattern
The correct choice is the last option
g(x) = 1/2*(4)^(–x) and
Please, see attached picture.
Your full question is attached in the picture below
To easily solve this problem, we can graph each equation and see, which one represents a reflection of the function over the y axis.
See, second image.
The answers are
the answer is not 65 and not 4
The graph of the function starts from (1,4) and moves up right.
The given rational function is
The base of this function is
The -1 under radical sign means the graph of the base function is shifted 1 unit right.
The +4 shows that base function is shifted up by 4 units.
The graph of the function therefore starts from (1,4) and moves up right.
Looking at the given points on the right side from (0,2) to (1,6) for 1 increase in X ( 1-0=1) the Y value increases by 3 ( 6/2 = 3)
This same increase happens for th other two points: 18/6 = 3
54 / 18 = 3
The rate of increase is 3.